SURVIE TERHADAP MOTOR ABILITY PADA SISWA KELAS II SD NEGERI 24 PONTIANAK TENGGARA - Runggah, Oktavianus; Atiq, Ahmad; Hidasari, Fitri Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The problem in this research is how the motor ability in SD Negeri 24 Southeast Pontianak. This study aims to determine the motor ability in SD Negeri 24 Southeast Pontianak. The method used in this research is to use the Descriptive method and the form of this research survey test and measurement The population in this study is grade II students of SD Negeri 24 Southeast Pontianak with a total of 43 students. The sample used was 43 students. The implementation of this research uses a test and measurement of motor ability consisting of: a 4x10 shuttle run test, 1 meter ball throwing test, balance test, 30 meter running test. The data analysis technique in this study used the percentage descriptive statistical calculation method. Based on the results of research in SD Negeri 24 class II Southeast Pontianak. That the level of motor ability test for male students of class II and the achievement of the shuttle run test results of 4 x 10 meters is less 16%, the ball throwing test is 1% less 18%, the balance test is 18% enough, and the 30 meter run test is sufficient 20%, female students achieving 4 x 10 meter shuttle run test results less 16%, ball throwing test distance of 1 meter less 20%, enough balance test 18% and 30 meters running test good 20%. Keywords:Motor Ability